Tourism Potential of the Gawai Tradition Talang Mamak Tribe in the village of Rantau Langsat - Beni Ismarizal; Enok Maryani (JURUSAN MANAJEMEN PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI GORONTALO, 2023)
The study aims to explore the tourism potential of Gawai (marriage celebration) ethnic tradition Talang Mamak, and this provides the context for a deeper examination of the Mamak Talang tribal tradition as a tourist product. This research used descriptive methods with qualitative analysis techniques. This research utilizes both primary and secondary data. The results of the study found that the Gawai tradition in Rantau Langsat village has the potential to become one of the leading tours in Rantau Langsat village which can become the basis for developing tourism in the area. The condition of infrastructure and supporting facilities in Rantau Langsat village, such as accommodation, restaurants and transportation can increase comfort and convenience for tourists visiting Rantau Langsat village.